2022
DOI: 10.1021/jacs.1c10842
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Polishing of Perovskite Surface Enhances Photovoltaic Performances

Abstract: The benefits of excess PbI 2 on perovskite crystal nucleation and growth are countered by the photoinstability of interfacial PbI 2 in perovskite solar cells (PSCs). Here we report a simple chemical polishing strategy to rip PbI 2 crystals off the perovskite surface to decouple these two opposing effects. The chemical polishing results in a favorable perovskite surface exhibiting enhanced luminescence, prolonged carrier lifetimes, suppressed ion migration, and better energy level alignment. These desired benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
98
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(103 citation statements)
references
References 44 publications
5
98
0
Order By: Relevance
“…More detailed illustrations of the synthetic routes from corannulenes to ACIs can be found in Schemes S1 and S2 in the Supporting Information. For the sake of comparison, three other π-conjugated ionic compounds were also selected for PSC fabrication, including two commercially available phenyl-based ammonium salts (phenylammonium iodide (PhAI) and phenmethylammonium iodide (PhMAI)) , and a home-synthesized fullerene-based ammonium salt (FuAI) based on our previous works (Figure S1). , As displayed in Figures S2–S5, all synthesized corannulene-derived compounds in this work were unambiguously characterized by 1 H NMR spectroscopy, 13 C NMR spectroscopy, and mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…More detailed illustrations of the synthetic routes from corannulenes to ACIs can be found in Schemes S1 and S2 in the Supporting Information. For the sake of comparison, three other π-conjugated ionic compounds were also selected for PSC fabrication, including two commercially available phenyl-based ammonium salts (phenylammonium iodide (PhAI) and phenmethylammonium iodide (PhMAI)) , and a home-synthesized fullerene-based ammonium salt (FuAI) based on our previous works (Figure S1). , As displayed in Figures S2–S5, all synthesized corannulene-derived compounds in this work were unambiguously characterized by 1 H NMR spectroscopy, 13 C NMR spectroscopy, and mass spectrometry.…”
Section: Resultsmentioning
confidence: 99%
“…One effective strategy is incorporation of smaller‐sized cations and anion, such as Cs + , MA + , and Br − , to stabilize α‐FAPbI 3 by regulating the Goldschmidt tolerance factor of perovskite. [ 20,29–31 ] However, the introduction of Cs + , MA + , and Br − comes at the cost of a blueshifted absorption spectrum, limiting the further enhancement of PCE. Furthermore, it was also found that Br − can cause phase segregation under long‐term illumination.…”
Section: Introductionmentioning
confidence: 99%
“…With the application of temperature, negligible PbI 2 appeared, which according to previous reports can act as an additional additive to passivate defects. 44,45 Besides, the effect of the imprinting pressure on the crystallinity of the perovskite layers was also verified (Figure S14). It was obviously that the crystallinity and orientation increased with the pressure.…”
Section: ■ Results and Discussionmentioning
confidence: 99%